P‐144: Sub‐millisecond Switching of Polymer‐stabilized Liquid Crystals with Crossed Patterned Electrodes. Issue 1 (May 2017) - Huh, Jae-Won; Ji, Seong-Min; Heo, Joon; Yoon, Tae-Hoon
Abstract : We report switching of polymer‐stabilized liquid crystals (PSLCs) with crossed interdigitated electrodes. A PSLC cell with crossed interdigitated electrodes is switchable between the transparent and opaque states, and it exhibits a sub‐millisecond response time and a low operating voltage. In the transparent state, a PSLC cell driven with crossed interdigitated electrodes has high specular transmittance and low haze; in the opaque state, it has low specular transmittance and high haze. The measured turn‐on and turn‐off time of the fabricated PSLC cells were 0.47 ms and 0.46 ms, respectively. We expect that a PSLC cell driven with crossed interdigitated electrodes can be applied to window display applications.